"IN THE CONDITIONS OF GLOBALIZATION". "SCIENTIFIC-THEORETICAL BASES OF PSYCHOCORRECTION OF ANXIETY IN PRESCHOOL AGE CHILDREN BASED ON GAME TECHNOLOGIES". (Universal International Scientific Journal, 2026)
This study is aimed at studying anxiety states in preschool children in the context of globalization and highlighting the scientific and theoretical foundations of their psychocorrection based on game technologies. As globalization processes introduce new requirements and approaches to the education system, ensuring the mental health of children is emerging as one of the urgent problems. Especially in preschool age, emotional instability and anxiety states can have a negative impact on personal development. The study analyzes the psychological nature of anxiety, its factors of origin and its role in the development of preschool children. Also, the psychocorrection capabilities of game technologies and the mechanisms of their influence on the emotional state of children are scientifically substantiated. The features of game activities that provide freedom, motivation and socialization are considered as an effective means of reducing anxiety.
Keywords: globalization, preschool education, mental health, anxiety, psychocorrection, game technologies, emotional development, psychological and pedagogical approaches, innovative methods, child psychology, psychological well-being, socialization, psychodiagnostics, correctional work